PROTECTION GUARANTEES FOR WHISTLEBLOWERS REGARDING INFORMATION ON NARCOTICS ABUSE BY THE COMMUNITY - Riana Putra Intaran, Galih; Bagiastra, I Nyoman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Purpose of the article This is to provide an overview of drug abuse regulations in Indonesia and explain protection for whistleblowers related to providing information on drug abuse. The methodology used in the article, which discusses the guarantee of protection given to whistleblowers regarding the provision of information about drug abuse, uses normative legal research, using a statutory legal approach in analyzing the legal issues discussed. In the end, specifically, Drug abuse is regulated in the Narcotics Law. Drug abuse is also regulated by other regulations, namely Supreme Court Circular No. 4 of 2010. However, the Supreme Court Circular only regulates the "placement of drug abusers, victims of abuse and drug addicts for medical and social rehabilitation." Apart from that, the form of regulation is still in the form of Supreme Court Circular which is limited to the scope of the Supreme Court Law. So far, there have been no special regulations that guarantee the protection of whistleblowers, especially against drug crimes. Therefore, these regulations must be presented as a law to ensure legal certainty. However, criminal reporting is regulated by Supreme Court Circular No. 4 of 2011. However, this regulation must provide certainty about what guarantees the state will provide to these whistleblowers. There still need to be more standards in the Narcotics Law and Supreme Court Circular No. 4/2011.